2011
DOI: 10.1111/j.1365-2702.2011.03697.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of leadership and ward factors on job satisfaction in nursing homes: a multilevel approach

Abstract: The study highlights the importance of using different leadership behaviour and the importance of high staff stability to ensure job satisfaction among nursing home personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 34 publications
6
30
0
6
Order By: Relevance
“…When analyzing the expectations of nursing teams in face of leadership, the interviewed professionals mentioned that future leaders need to be people who allow frank and open communication, have the capacity to recognize and attend to the needs of teams, know how to give support when needed, and seek harmony in the work environment, working for the union and integration of the group and ensuring the satisfaction of those led. (33) Ten other studies (10,11,(14)(15)(16)18,(20)(21)(22)34) showed positive and significant, direct correlations between the different leadership styles analyzed and job satisfaction; that is, as leadership is exercised and perceived, there is an increase in job satisfaction. The influence of leadership style in the work environment is well-known, because it can lead to synergy or disintegration of teams.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…When analyzing the expectations of nursing teams in face of leadership, the interviewed professionals mentioned that future leaders need to be people who allow frank and open communication, have the capacity to recognize and attend to the needs of teams, know how to give support when needed, and seek harmony in the work environment, working for the union and integration of the group and ensuring the satisfaction of those led. (33) Ten other studies (10,11,(14)(15)(16)18,(20)(21)(22)34) showed positive and significant, direct correlations between the different leadership styles analyzed and job satisfaction; that is, as leadership is exercised and perceived, there is an increase in job satisfaction. The influence of leadership style in the work environment is well-known, because it can lead to synergy or disintegration of teams.…”
Section: Discussionmentioning
confidence: 85%
“…The article that adopted this framework referred to a positive correlation between job satisfaction and task-oriented leadership styles and relationships, with a stronger effect on task orientation. (18) Finally, no studies were found that established relationships between some contemporary leadership theories and job satisfaction. An example is charismatic leadership (based on personal quali-The Leadership Practice Inventory, used in the article developed in the United States (21) and China, (19) measures the perception of the transformational leadership practices of the exemplary leader.…”
Section: Discussionmentioning
confidence: 99%
“…Although corrective leaders focus on monitoring, correcting, and punishment, leaders with the constructive style clarify expectations and provide recognition when goals are achieved. 47,48 The authors argue such leadership style provides staff with structure, coordination, and clarification of roles and expectations, and is, therefore, particularly relevant in a work environment where the majority of staff are unlicensed, have low level of autonomy, and require more direction and support from supervisors. 29 For example, a recent cross-sectional study of 40 nursing home wards in Norway has demonstrated the importance of active, task-oriented leadership, which shares similar characteristics with the constructive style of transactional leadership, in improving care quality and staff job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors of job satisfaction researches see the essence of the approach to different aspects of the employment situation, many of which have social and psychological nature (Nakonecny, 2005;Kollarik, 2010;Malloy, & Penprase, 2010). There are also studies that seek to affect the relationship between job satisfaction and organizational culture (Lovas, 2007;Fleskova, & Podolcova, 2010), socially responsible business and job satisfaction (Vagnerova, 2007;Fleskova, 2011) but also between the job satisfaction and the leadership style of the working group (Havig, Skogstad, Veenstra, & Romoren, 2011).…”
Section: Introductionmentioning
confidence: 96%